2015
DOI: 10.1080/07370016.2015.1024541
|View full text |Cite
|
Sign up to set email alerts
|

Breast Health Beliefs, Behaviors, and Barriers Among Latina Permanent Resident and Migratory Farm Workers

Abstract: There is a dearth of research on the breast health behaviors of migratory farm workers. This research used focus group methodology to compare the breast cancer beliefs and barriers of Latina women working as migratory farmers (n = 33) and permanent residents (n = 31). In comparison to their permanent resident counterparts, migrant farmers had low knowledge about the causes of breast cancer, and experienced significant barriers to care. Many barriers were cultural-specific, including culturally-based gender rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…14 Other research examined breast cancer knowledge through the nuanced lens of Latina migratory farm workers vs. Latina permanent residents and found that, compared to permanent residents, migrant farmworkers demonstrated significantly lower breast cancer knowledge. 15 There is a dearth of research on the breast health behaviors of migratory farm workers. This research used focus group methodology to compare the breast cancer beliefs and barriers of Latina women working as migratory farmers (n = 33) and permanent residents (n = 31).…”
Section: Discussionmentioning
confidence: 99%
“…14 Other research examined breast cancer knowledge through the nuanced lens of Latina migratory farm workers vs. Latina permanent residents and found that, compared to permanent residents, migrant farmworkers demonstrated significantly lower breast cancer knowledge. 15 There is a dearth of research on the breast health behaviors of migratory farm workers. This research used focus group methodology to compare the breast cancer beliefs and barriers of Latina women working as migratory farmers (n = 33) and permanent residents (n = 31).…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 38 Information on Hispanic-origin Spanish-speaking immigrants to the United States and breast cancer screening knowledge has largely focused on destination of immigrant and occupation. 6 , 7 , 20 , 35 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Although insurance status, income, and education levels are the most consistent predictors of preventive screening behaviors among Mexican Americans, 2 , 3 breast cancer screening depends on heavily on the type of information available on risk in this population. 4 – 8 There has been less consistent evidence that cultural and social barriers impede on Hispanic women’s follow-through in being screened. 3 Nevertheless, interventions to increase mammogram utilization in Hispanic women have generally focused on increasing breast cancer screening knowledge, self-efficacy, or decreased real or perceived barriers to screening.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based participatory research (CBPR) facilitates collaborative research partnerships that enable meaningful consideration of sociocultural context [21], and has been successfully conducted with farmworker communities around the US to study and address occupational hazards like pesticide exposure [22][23][24][25][26][27][28][29][30], and to promote mental and physical health promotion and healthcare utilization [31][32][33][34][35]. Numerous community-based studies related to breast cancer have evidenced barriers to care for Spanish-speaking Latina farmworkers including fear, stigma, low education and health literacy levels, and have stressed the importance of targeted outreach strategies and the involvement of community members in the development and implementation of education and screening interventions to ensure that specific needs are met [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%